The Doctrine of Product Liability and Negligence Cannot Be Applied to Malware-Embedded Software - Suran Ningsih, Ayup (JILS (Journal of Indonesian Legal Studies), 2019)
Today, the development of technology is remarkable; the world has faced the industrial era 4.0 where people are now more popular to carry out various financial transactions, both the process of buying and selling and other financial transactions through digital transactions. This digital transaction is run by an information system and is provided with special software that runs it. Damage to computer devices and software can cause all kinds of damage. This damage can cause someone to experience damage or loss due to damaged hardware or software, one or more of the following legal areas can provide recovery; such as contract law; technology law; consumer protection; and product liability. This article is to examine the doctrine of product liability and negligence cannot be applied to malware-embedded software. The approach of the research method used in this article is normative juridical. The normative juridical approach is an approach carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research.